Impact of prenatal triclosan exposure on ADHD-like symptoms in school-aged children - Jingjing LI; Xiaomeng CHENG; Yan ZHANG; Luanluan LI; Xiaodan YU; Ying TIAN; Yu GAO (环境与职业医学)
BackgroundAttention-deficit hyperactivity disorder (ADHD) is a common neurodevelopmental and behavioral disorder in children, often diagnosed during school age. The etiology of ADHD remains unclear; however, existing studies suggest that environmental factors, such as exposure to triclosan (TCS), may be associated with the occurrence of ADHD-like symptoms in offspring. Nevertheless, relevant research in China remains limited.ObjectiveTo investigate the impact of early pregnancy TCS exposure on ADHD-like symptoms in 7-year-old children.MethodsThis study was based on the Shanghai Birth Cohort (SBC) and included 662 mother-child pairs. TCS concentrations in early pregnancy urine samples were measured using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS). Demographic information was collected via questionnaires and medical record abstraction. ADHD-like symptoms in 7-year-old children were first assessed using the Strengths and Difficulties Questionnaire (SDQ). Further differentiation of ADHD-like symptom subtypes (inattentive and hyperactive/impulsive) was conducted using the SNAP-IV, a clinically validated ADHD screening tool. Negative binomial regression models were applied to evaluate the associations between prenatal TCS exposure and hyperactive behavior (SDQ assessment) as well as ADHD-like symptom subtypes (SNAP-IV assessment) in 7-year-old children.ResultsThe positive rate of TCS in early pregnancy urine samples was 91.39%, with median concentrations of 0.69 μg·L−1 and 0.63 μg·g−1 before and after the creatinine adjustment, respectively. The modeling results indicated that prenatal TCS exposure was associated with an increased risk of hyperactive symptoms (SDQ assessment) in 7-year-old children (RR=1.04, 95%CI: 1.02, 1.06); the stratified analyses by children sex revealed similar effects for both boys (RR=1.04, 95%CI: 1.02, 1.07) and girls (RR=1.04, 95%CI: 1.01, 1.07). Further analysis of ADHD-like symptom subtypes showed that prenatal TCS exposure increased the risk of inattentive symptoms (RR=1.03, 95%CI: 1.00, 1.05); the sex-stratified analyses indicated associations between TCS exposure and inattentive symptoms (RR=1.03, 95%CI: 1.00, 1.07) as well as hyperactive/impulsive symptoms (RR=1.04, 95%CI: 1.01, 1.08) in girls.ConclusionPrenatal TCS exposure is associated with an increased risk of ADHD-like symptoms in 7-year-old children, primarily contributing to the risk of the inattention subtype. The impact is more pronounced in girls.